Nordic hamstring exercises in functional knee rehabilitation after anterior cruciate ligament reconstruction: a prospective, randomised, controlled study - JiaWei Chen; TianYu Wu; Ying Guo (Scientific Reports, 2023)
Abstract To study the effect of using Nordic hamstring exercise method on muscle strength and knee joint stability of patients after ACL reconstruction. 60 patients admitted to our hospital for ACL reconstruction were randomly divided into a test group (n = 30, applying Nordic hamstring exercise) and a control group (n = 30, applying conventional rehabilitation training methods), and the difference in the circumference of the thighs of the patients in the two groups was analysed after training, and the peak torque (PT), total torque (PT), and flexion and extension strength were measured by using the Biodex system3 Multi-joint Isokinetic Testing System at knee joints with an angular velocity of 60°/s and 120°/s. The peak torque (PT), total work (TW), and average peak torque (AVG PT) were measured by extension and flexion strength at angular velocity, and the Lysholm Knee Score was used to assess the knee function of 60 patients. There was no difference in the difference in thigh circumference between the two groups before surgery (P > 0.05); the difference in thigh circumference between the patients in the test group at 12 and 24 weeks after surgery was (− 0.35 ± 0.22) cm and (0.12 ± 0.03) cm, respectively, which were higher than those in the control group, (− 0.51 ± 0.15) cm and (− 0.41 ± 0.34) cm (P < 0.05). At the 12th and 24th postoperative weeks, the popliteal muscle strength of both groups was improved compared with that before surgery; among them, by comparing the popliteal peak moments with different angular velocities, the ratio of popliteal peak moment on the affected side/peak moment on the healthy side of the popliteal muscle of the experimental group was significantly higher than that of the control group, and the difference was significant (P < 0.05), but there was still a gap compared with that of the healthy side. The Lachmen test and the anterior drawer test were negative in the test and control groups at the 24th postoperative week of review, and the anterior tibial shift was < 5 mm in the KT-1000 test, and the difference in the anterior shift was < 3 mm compared with the healthy side, and there was no significant difference between the two groups. By Nordic hamstring exercise can make patients after knee ACL reconstruction reduce patient pain, accelerate the recovery of knee function, improve the swelling of the lower limb, reach the level of flexor strength of the healthy side within 24 weeks, and can increase the stability of the knee joint.